A SENSE OF HUMOR HANNIBAL - Alexander Pavlovich Belikov (Вестник Северо-Кавказского федерального университета)
The article is devoted to the subject, virtually untouched in the world historiography: the personal characteristics of the great Carthaginian general Hannibal, showing him with a rather unexpected source.